Effectiveness of insecticides against the adult stage of western corn beetle (Diabrotica virgifera virgifera LeConte, 1868) - V. Saliienko; V. Fedorenko (Карантин і захист рослин)
Goal. Assessment of chemical insecticides for WCR (Diabrotica virgifera virgifera LeConte, 1868) adults control for using in integrated corn pest management systems.